Formation in Family and Educational Institutions of Orthodox Form of Thinking and Communication (Global Journal of Human-Social Science, 2023)
Man is the interconnection of spirit, mind, soul and body. The body is the dwelling of the soul. The soul is the dwelling of the spirit, the source of life of the body, desires and feelings of man. The mind gives rise to thoughts and carries out their linguistic design. Thought is of a spiritual nature. The spirit penetrates into the living information of nature, into the soul and body, communicates with the spirits of other people. Jesus communicated with spirits. The human spirit communicates through prayer with God as a spiritual entity. He is the spiritual, moral, moral and ethical leader of the thinking, behavior and being of a person. Mind, spirit, soul and memory form a person in the process of human life. A person thinks and has spiritual qualities. Psalm 18:3 describes the nature of thinking. The night of the night reveals knowledge by penetrating the spirit into the living information of nature. Day to day conveys speech (communication) based on existing language knowledge.
Keywords: spiritual thinking; orthodox form of communication; quality of spirit; education in educational institutions